Pengaruh Variasi Konsentrasi Cera Alba sebagai Stiffening Agent pada Lip Balm Ekstrak Buah Parijoto (Medinilla speciosa Blume): The Effect of Cera Alba Concentration Variations as a Stiffening Agent in Parijoto Fruit (Medinilla speciosa Blume) Extract Lip Balm - Sinta Mutiara Dewi; Nur Cholis Endriyatno (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Parijoto fruit extract has antioxidant activity with an IC50 value of 19.73 ppm. Parijoto extract needs to be formulated into a lip balm to maximise its potential. Lip balm preparations require a stiffening agent used to maintain shape, texture, and stability. The stiffening agent used in this study is cera alba. The aim of this research is to determine the effect of varying concentrations of cera alba as a stiffening agent on the physical properties of lip balm preparations made from parijoto fruit extract (Medinila speciosa Blume). This research is an experimental study. The parijoto fruit extract was prepared by maceration extraction using 96% ethanol. The preparations were made with 3 formulas with different concentrations of cera alba as a stiffening agent: FI (10%), FII (15%), and FIII (20%). Subsequently, physical tests of the lip balm preparations were conducted, including organoleptic tests, pH tests, homogeneity tests, adhesion tests, spreadability tests, viscosity tests, moisture content tests, and irritation tests. The results of the physical property analysis of the lip balm preparations were analysed descriptively and inferentially using statistical software with one-way ANOVA and post hoc Tukey tests. Based on the results, the variation in cera alba concentration as a stiffening agent influences the physical properties of the lip balm extract from parijoto fruit (Medinila speciosa Blume), including pH, viscosity, adhesion, and spreadability, but does not significantly affect moisturising ability. In this study, FI with 10% cera alba concentration was established as the best formula based on the fulfilment of all physical property tests (pH, viscosity, adhesion, spreadability) and the statistical test results. Keywords: Parijoto fruit; Cera alba; Lip balm; Stiffening agent.